A esfera como metáfora: representações do futebol no campo da literatura (leituras do tema no conto de ficção) - Nascimento, Edônio Alves do (2011)
Football, understood as a phenomenon of sports practice and nearly universal coverage, can also be seen as a game whose operation circumvents the cultural universe of people who practice it. Much more than just a sport, so this game is a cultural phenomenon par excellence, bearing a communicational and aesthetic dimension whose occurrence has been spotted in various fields of scientific and cultural. Therefore, it is as game and as a phenomenon of culture, we intend to focus on football here as an object of study. Our aim is to investigate the sport in Brazil taking the Literature and Journalism as privileged instances of their representation in the media. Thus, the central idea of this research is to show when and how football has become a recurrent theme in Brazilian literature, starting with its journalistic approach until we get an overview of the aesthetic representation of the game, Literature as the main focus of attention and taking the genre of fiction story as material fact of their representation. With this approach, we intend to develop an overall view, overview of the literature about football in our country and at the same time, particularize this vision in some representative authors of it, like the writer-journalist Mario Filho (the historian, essayist on the modernization of chronic specific theme), José Lins do Rego (writer passionate about the game), Nelson Rodrigues (the esthetician that elevated the sport to the status of art by chronic), Lima Barreto (who along with Antonio de Alcantara Machado pioneered the formalized within the fiction) and the storytellers of the topic itself. In the end, we intend to infer the results of evaluations and reviews of books and authors listed, we have examined a wide sense, but also vertical (and which were focused on a socio-historical perspective and critical-aesthetic) within the assumption that seems be a homology between the way football practice amongst us will historically winning characteristics as to form a Brazilian school of football, and how our writers, journalists will be addressing the topic, which also would focus on creating a "Brazilian way" of telling literary football. The proof of this hypothesis operational work together with the development of historiography and the necessity arising from it, creating a "Guide to Reading football theme in fictional tale of Brazil" shut the focal perspective of this study